Irrigation: Remote control - Zwart, Sander J.; Leclert, Lucie M.C.; Bastiaanssen, Wim G.M. (Technical Centre for Agricultural and Rural Cooperation, 2010)
Managers of the Office du Niger irrigation scheme in Mali are using remote sensing data to analyse the efficiency of the system without having to physically check the infrastructure. The information will help them prepare for future expansion.